(3x-3)(x-3)=(2x-1)(2x-1)(2x)

Simple and best practice solution for (3x-3)(x-3)=(2x-1)(2x-1)(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-3)(x-3)=(2x-1)(2x-1)(2x) equation:


Simplifying
(3x + -3)(x + -3) = (2x + -1)(2x + -1)(2x)

Reorder the terms:
(-3 + 3x)(x + -3) = (2x + -1)(2x + -1)(2x)

Reorder the terms:
(-3 + 3x)(-3 + x) = (2x + -1)(2x + -1)(2x)

Multiply (-3 + 3x) * (-3 + x)
(-3(-3 + x) + 3x * (-3 + x)) = (2x + -1)(2x + -1)(2x)
((-3 * -3 + x * -3) + 3x * (-3 + x)) = (2x + -1)(2x + -1)(2x)
((9 + -3x) + 3x * (-3 + x)) = (2x + -1)(2x + -1)(2x)
(9 + -3x + (-3 * 3x + x * 3x)) = (2x + -1)(2x + -1)(2x)
(9 + -3x + (-9x + 3x2)) = (2x + -1)(2x + -1)(2x)

Combine like terms: -3x + -9x = -12x
(9 + -12x + 3x2) = (2x + -1)(2x + -1)(2x)

Reorder the terms:
9 + -12x + 3x2 = (-1 + 2x)(2x + -1)(2x)

Reorder the terms:
9 + -12x + 3x2 = (-1 + 2x)(-1 + 2x)(2x)

Remove parenthesis around (2x)
9 + -12x + 3x2 = (-1 + 2x)(-1 + 2x) * 2x

Reorder the terms for easier multiplication:
9 + -12x + 3x2 = 2x(-1 + 2x)(-1 + 2x)

Multiply (-1 + 2x) * (-1 + 2x)
9 + -12x + 3x2 = 2x(-1(-1 + 2x) + 2x * (-1 + 2x))
9 + -12x + 3x2 = 2x((-1 * -1 + 2x * -1) + 2x * (-1 + 2x))
9 + -12x + 3x2 = 2x((1 + -2x) + 2x * (-1 + 2x))
9 + -12x + 3x2 = 2x(1 + -2x + (-1 * 2x + 2x * 2x))
9 + -12x + 3x2 = 2x(1 + -2x + (-2x + 4x2))

Combine like terms: -2x + -2x = -4x
9 + -12x + 3x2 = 2x(1 + -4x + 4x2)
9 + -12x + 3x2 = (1 * 2x + -4x * 2x + 4x2 * 2x)
9 + -12x + 3x2 = (2x + -8x2 + 8x3)

Solving
9 + -12x + 3x2 = 2x + -8x2 + 8x3

Solving for variable 'x'.

Reorder the terms:
9 + -12x + -2x + 3x2 + 8x2 + -8x3 = 2x + -8x2 + 8x3 + -2x + 8x2 + -8x3

Combine like terms: -12x + -2x = -14x
9 + -14x + 3x2 + 8x2 + -8x3 = 2x + -8x2 + 8x3 + -2x + 8x2 + -8x3

Combine like terms: 3x2 + 8x2 = 11x2
9 + -14x + 11x2 + -8x3 = 2x + -8x2 + 8x3 + -2x + 8x2 + -8x3

Reorder the terms:
9 + -14x + 11x2 + -8x3 = 2x + -2x + -8x2 + 8x2 + 8x3 + -8x3

Combine like terms: 2x + -2x = 0
9 + -14x + 11x2 + -8x3 = 0 + -8x2 + 8x2 + 8x3 + -8x3
9 + -14x + 11x2 + -8x3 = -8x2 + 8x2 + 8x3 + -8x3

Combine like terms: -8x2 + 8x2 = 0
9 + -14x + 11x2 + -8x3 = 0 + 8x3 + -8x3
9 + -14x + 11x2 + -8x3 = 8x3 + -8x3

Combine like terms: 8x3 + -8x3 = 0
9 + -14x + 11x2 + -8x3 = 0

The solution to this equation could not be determined.

See similar equations:

| -n+(5n-7)=-5 | | 21x^2+11x-40=0 | | e^24=5x+1 | | 2x+3(x-5)+12=37 | | 2x+6+3x=3x+3 | | 5c+25= | | 3x^12+54x^7+51x^2=0 | | 3x^12+54x^7=51x^2 | | 4.95*2+m=.15+4m | | 78x^2+42x=0 | | 10+16x=42+8x | | 4-2x+2=12 | | 2(-x-y)=2(-3) | | 10x^4-10=0 | | 125=45+8x | | -77.4=9x | | 0=(x^3)-(9x^2)+1 | | 61=12x-107 | | 6x+24=3x-3 | | 58=4x+20 | | 4(x+7)=8+2x | | 4x+2(-2x+4)+8=8 | | 0.75(x)+1.25=-0.25 | | 7(z+8)-(1-5z)=11z | | 19y=18(y+3) | | -17+2x=13 | | -5X^4Y^3= | | p-0.15=11.01 | | 2y+1(22)= | | a=6+-2b | | 21=6x-33 | | 88-2b=-16b-22 |

Equations solver categories